Kuy Learn to Pray Application to Train the Practice of Prayer in Children - Ryan Apriansyah; Hamdani Ali Mukti; Imam Tabroni; Li Jie; Guijiao Zou (Journal Emerging Technologies in Education, 2023)
Background. This research aims to create an android application-based prayer learning media product to train and teach prayer to children. This research uses a type of development research or known as Research & Development (R&D). Purpose. The development model used in this research refers to the Borg and Gall development model. Method. The research process begins with a preliminary study to see the problems that occur, the potential for development, determining the literature review relevant to the problems that occur to plan the manufacture of the initial product design, initial product field trials. Results. , product revision I, main field trials, product revision II, operational field trials. Conclusion. final product revision and dissemination and implementation of product application. The results of the research on the use of the Kuy Belajar Shalat Application developed in this study with a series of steps and stages of trials can be said to be effective for training children in learning prayers because there is an increase in scores in each trial conducted